1998
DOI: 10.3171/foc.1998.5.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical anatomy of the artery of Adamkiewicz and its segmental artery

Abstract: Object The blood supply of the lower spinal cord is heavily dependent on the artery of Adamkiewicz, which characteristically originates from one of the thoracolumbar segmental arteries. The aforementioned artery is of enormous clinical, surgical, and radiological importance, and the goal of this study was to elucidate the course and branches of the segmental artery that gives rise to this important vessel. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 3 publications
1
38
0
1
Order By: Relevance
“…The specific neural foraminal level and laterality of the artery of Adamkiewicz is highly variable: it most often originates between the T9 and L3 levels and usually on the left, but origins from as high as the T2 level and as low as the S2 level have been described (17)(18)(19)(20)(21)(22). In practice, the proceduralist must assume that the artery of Adamkiewicz could be present in any thoracic, lumbar, or upper sacral neural foramen.…”
Section: Discussionmentioning
confidence: 99%
“…The specific neural foraminal level and laterality of the artery of Adamkiewicz is highly variable: it most often originates between the T9 and L3 levels and usually on the left, but origins from as high as the T2 level and as low as the S2 level have been described (17)(18)(19)(20)(21)(22). In practice, the proceduralist must assume that the artery of Adamkiewicz could be present in any thoracic, lumbar, or upper sacral neural foramen.…”
Section: Discussionmentioning
confidence: 99%
“…The ASA varies in size from approximately 0.5 to 0.8 mm in the thoracolumbar region. 4 Its greatest diameter is at the level of its conjunction with AKA, and usually measures 0.5-0.8 mm, but may be as large as 1.0 mm. 4 In the thoracolumbar region, the course of the ASA varies from straight (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1, 2). [3][4][5] Preoperative anatomical evaluation of the AKA is essential in many clinical disciplines: vascular surgery (aortic aneurysms), neurosurgery (intramedullary tumors), as well as urology and pediatric surgery (retroperitoneal dissections), because it helps avoid serious neurological complications such as paraplegia or paraparesis. 1,2 The aim of this study was to evaluate the detection of the AKA, as well as its level and the side of origin, with multi-detector contrast enhanced computed tomography (MDCT) of the abdomen and thorax performed during everyday clinical practice, and to compare the results with the literature.…”
mentioning
confidence: 99%
“…18 Lazorthes et al 18 have noted a T9-12 origin in 74% of cases, between T5 and T8 in 15%, and from L1 to L2 in 10%. Alleyne et al 1 have reported a leftsided origin in 78% of cases and an origin branching from T9 to T12 in 60% of cases, from L1 in 25%, and from T5 to T8 in 15%. The leftsided predominance was most prob ably due to an aorta located on the left side.…”
Section: Understanding the Anatomy Of The Adamkiewicz Arterymentioning
confidence: 99%